Pengaruh Media Youtube pada Pembelajaran Menulis Teks Eksposisi Siswa Kelas VIII SMP Negeri 2 PematangsiantarPengaruh Media Youtube pada Pembelajaran Menulis Teks Eksposisi Siswa Kelas VIII SMP Negeri 2 Pematangsiantar - Vivi Imelda Simangunsong; Junifer Siregar; Jumaria Sirait (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
Learning to write needs to be mastered by students as early as possible, especially in the text-based 2013 curriculum. One of the materials related to the exposition text is found in the syllabus of the Indonesian language subject for class VIII, in learning media is needed that is able to arouse students' enthusiasm. The problem studied in this study is how the influence of youtube media in learning to write student exposition texts. This study aims to determine the effect of youtube media in learning to write exposition texts for seventh grade students of SMP Negeri 2 Pematangsiantar. The use of youtube media is expected to make it easier for students to understand the material and be able to write exposition texts. This research is a quantitative experiment. With one group pre-test and post-test design. The researcher used random sampling technique in determining the sample so that class VIII-10 students became the sample in this study. This research was conducted at SMP Negeri 2 Pematangsiantar. The technique of collecting data in this study used an exposition text writing test. Data on students' exposition text writing activities in the study were obtained through pre-test and post-test. Based on the results of data analysis, it can be seen that the average score of students before using the youtube learning media (pre-test) is categorized with a value of 41.1 and the average value after using the youtube learning model (post-test) is categorized as good with a value of 73,06, then the results of the average value of the pre-test and post-test can be seen that there is a difference in the average value before (pre-test) and after using youtube learning media on the ability to write exposition texts for class VIII students of SMP Negeri 2 Pematangsiantar. Based on the results of the pre-test and post-test data analysis, it was obtained tcount (16,732) , then compared tcount with ttable with degrees of freedom N-1 = 29 with the number of N=30 and the significant level = 0.05, it was obtained ttablel =1, 699. So, tcount (16,732) > ttable (1, 699) which means that there is a difference in the average value before using youtube learning media and after using youtube learning media. Thus Ho is rejected. With the rejection of Ho then Ha is accepted, meaning that there is a significant difference in the skills of writing exposition texts for class VIII SMP Negeri 2 Pematangsiantar students using youtube learning media.